Part IX – September 1968 - Communications - Elements of V Group as Modifiers of Aluminum-Silicon Alloys - N. R. Pillai; T. R. Anantharaman (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1969)
THE striking alterations in the constitution and structure of cast A1-Si alloys brought about by addition of small quantities of some elements, particularly sodium, have been extensively investigated. Many theories' have also been propounded to explain this so-called lLmodification" process, but their main concern has been more to throw light on the action of sodium than to arrive at general criteria underlying this interesting as well as intriguing phenomenon. Such theories have generally dealt with one or more, but not all, factors that seem to have a direct or indirect influence on the cast structure of A1-Si alloys, e.g.., formation of ternary eutectic, removal of oxides, hydroxides, and so forth, by fluxing, morphological changes in silicon, and inhibition of growth of silicon grains through colloidal action, compound formation, preferential adsorption, or reduction of surface tension. Kim and Heine2 were the first to study the modification of A1-Si alloys in a systematic as well as comprehensive manner and to list the important characteristics of a satisfactory modifier. According to them, an important property of the modifying element is its capacity to form a stable compound with silicon in the appropriate temperature range. Other subsidiary requirements are that the element should get adequately dispersed in the melt at the inoculating temperature and also must not form stable compounds with aluminum. The alkali elements, with the exception of lithium, fulfill these requirements most satisfactorily and have been shown to be successful modifiers by these workers. Sodium is the most effective of these and seems to be in a class by itself for various reasons noted by earlier investigators.37 None of the other elements tried by Kim and Heine, viz., Mg, Ca, Cd, Zn, In, Pb, P, As, Bi, S, and Se, showed any significant modifying action. We wish to report here briefly on substantial modifications in cast eutectic A1-Si alloys brought about by some V group elements, which do not comply with the Kim-Heine requirements. Aluminum and silicon used in the present work were indigenous and had purities of 99.8 and 99.5 pct, re-